The Prenatal Morphomechanic Impact of Agenesis of the Corpus Callosum on Human Brain Structure and Asymmetry. (19th April 2021) - Schwartz, Ernst; Diogo, Mariana Cardoso; Glatter, Sarah; Seidl, Rainer; Brugger, Peter C; Gruber, Gerlinde M; Kiss, Herbert; Nenning, Karl-Heinz; ,; Langs, Georg; Prayer, Daniela; Kasprian, Gregor
Abstract: Genetic, molecular, and physical forces together impact brain morphogenesis. The early impact of deficient midline crossing in agenesis of the Corpus Callosum (ACC) on prenatal human brain development and architecture is widely unknown. Here we analyze the changes of brain structure in 46 fetuses with ACC in vivo to identify their deviations from normal development. Cases of complete ACC show an increase in the thickness of the cerebral wall in the frontomedial regions and a reduction in the temporal, insular, medial occipital and lateral parietal regions, already present at midgestation. ACC is associated with a more symmetric configuration of the temporal lobes and increased frequency of atypical asymmetry patterns, indicating an early morphomechanic effect of callosal growth on human brain development affecting the thickness of the pallium along a ventro–dorsal gradient. Altered prenatal brain architecture in ACC emphasizes the importance of conformational forces introduced by emerging interhemispheric connectivity on the establishment of polygenically determined brain asymmetries.